DISTRIBUSI PENERIMA BANTUAN IURAN BAGI MASYARAKAT FAKIR MISKIN DAN KURANG MAMPU DI KELURAHAN PADANG MAS KABUPATEN TANAH KARO SUMATERA UTARA (TINJAUAN SIYASAH SYAR’IYAH) - Fatimah, Fatimah; Kurniawan, Mhd Fazar (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2022)
This study aims to analyze the distribution of the Social Security Administering Body for Contribution Assistance (BPJS PBI) programs for the poor and underprivileged in the Padang Mas sub-district, Tanah Karo Regency, North Sumatra, which has been on target or not and to review the position of the BPJS PBIâ€™s program in the Siyasah Syarâ€™iyah review.Â This study uses empirical legal research methods by analyzing the problems that have been formulated and the combination of primary, secondary and tertiary sources of library materials with primary data obtained in the field. The results of this study explain that the distribution of the BPJS PBIâ€™s program in Padang Mas Village, Tanah Karo Regency is carried out well even though there are shortcomings such as errors in collecting BPJS PBI membership data which resulted in the distribution being considered less targeted. The implementation of this program must be supported by several factors, such as: good communication, active community participation and equitable tracking of information so that the distribution of aid is more targeted. As for the BPJS PBIâ€™s program, when viewed from the Siyasah Syarâ€™iyah aspect, it turns out to be in accordance with the objectives of Siyasah Maliyah and Siyasah Duturiyah, namely both for the benefit of the people for the welfare of the citizens' lives for the better.